Leveraging business analysis for project success - James, Vicki (Project management specialist) (Portfolio and project management collection., 2019)
Only 39 percent of projects today are successful. Nearly half of the projects that fail do so because of "poor requirements management" (PMI 2014). Leveraging Business Analysis for Project Success, Second Edition explores the role of the business analyst in setting a project up for success. It informs and educates project managers, sponsors, and organization leaders on what is necessary for project success. This book goes beyond requirements management in exploring how business analysis professionals (business analysts, product managers, product owners, and others) can con- tribute to increased profitability through project selection, scope definition, and post implementation evaluation. The reader will learn about the history of business analysis, professional organizations and resources to support the profession, and what to expect from the business analysis professional at each phase of the project lifecycle as presented in a case study throughout the book. Project leaders will better be able to support the business analysis needs of the project by understanding the skills, expertise, tasks, resources, and time needed to do business analysis right and maximize the return on investment for each project